Managing risk in projects - Hillson, David, 1955- (Routledge, 2024)
"Projects are risky undertakings, and risk management is recognised as an integral part of managing the project. Managing Risk in Projects places risk management in its proper context in the world of project management and beyond, emphasising the central concepts essential to understanding why and how risk management matters, and presenting proven practical approaches to addressing risk in any project. The risk management world has changed significantly since the first edition, with advances in risk management practice reflected by changes in international standards and guidelines, as well as significant developments in their implementation. This second edition reflects these changes, and has been completely updated to address progress in the practical application of risk management to projects. Two new chapters have been added, the first discussing how to manage risk in complex projects, and the second considering the role and influence of risk leaders outside the project arena in setting the context and environment for successful risk management. New material also addresses enterprise risk management and risky decision-making. Throughout, the book offers a concise description of current best practice in project risk management whilst introducing the latest developments, to enable project managers, project sponsors and others responsible for managing risk on projects to do just that - effectively"-- Provided by publisher.
Keywords: Risk management.; Project management.; elektronické knihy; electronic books